Combination of Gabapentin and Vitamin B12 Compared with Gabapentin Monotherapy on Pain Improvement of Diabetic Neuropathy Patients - Mochamad Firdaus Bhuanaputra; Alya Tursina; Yuktiana Kharisma (Universitas Islam Bandung, 2020)
Diabetic neuropathy is the most common microvascular complication of diabetes mellitus (DM) occurring in 60–70% of the world's DM population, 40% of the DM population in Asia, and 41% of the DM population in Indonesia. The primary treatment of diabetic neuropathy pain in Indonesia is gabapentin and vitamin B12. The study aimed to compare pain improvements in diabetic neuropathy patients. The drug used was a combination of gabapentin and vitamin B12 and gabapentin monotherapy. For the pain degree measurement, we used the visual analogue scale (VAS). This experimental study was a pretest-posttest randomized control trial using a single-blind method at Dr. M. Salamun Air Force Hospital Bandung from March to May 2017. Samples were 44, type two diabetic neuropathy patients. The Mann-Whitney test to compare pain improvement between 2 groups applied. The results indicated there were differences in pain improvement between diabetic neuropathy patients with gabapentin and vitamin B12 combination compare to gabapentin monotherapy (p=0.002). This result showed a synergistic effect of gabapentin as an inhibitor of neurotransmitter and vitamin B12 expenditure as an improvement in peripheral nerve cells. This study concluded that gabapentin and vitamin B12 combination is better in improving pain in diabetic neuropathy patients compared to gabapentin monotherapy. KOMBINASI GABAPENTIN DAN VITAMIN B12 DIBANDING DENGAN MONOTERAPI GABAPENTIN TERHADAP PERBAIKAN NYERI PASIEN NEUROPATI DIABETIKNeuropati diabetik merupakan komplikasi mikrovaskular terbanyak diabetes melitus (DM) yang terjadi pada 60–70% populasi DM di dunia, 40% populasi DM di Asia, dan 41% populasi DM di Indonesia. Pengobatan utama nyeri neuropati diabetik di Indonesia adalah gabapentin dan vitamin B12. Tujuan penelitian ini membandingkan perbaikan rasa nyeri pada pasien neuropati diabetik. Obat yang diberikan adalah kombinasi gabapentin dan vitamin B12 serta monoterapi gabapentin. Pengukuran tingkat nyeri menggunakan visual analogue scale (VAS). Penelitian eksperimental ini adalah pretest-posttest randomized control trial dengan menggunakan metode single-blind yang dilakukan di RSAU Dr. M. Salamun Bandung dari bulan Maret hingga Mei 2017. Sampel berjumlah 44 jenis, dua pasien neuropati diabetik. Sampel berjumlah 44, pasien neuropati diabetik tipe dua. Uji Mann-Whitney dilakukan untuk membandingkan perbaikan nyeri antara 2 kelompok perlakuan. Hasil penelitian menunjukkan terdapat perbedaan perbaikan rasa nyeri pasien neuropati diabetik yang diberi pengobatan kombinasi gabapentin dan vitamin B12 dibanding dengan monoterapi gabapentin (p=0,002). Hasil ini menunjukkan efek sinergis gabapentin sebagai inhibitor neurotransmiter dan vitamin B12 yang berfungsi memperbaiki sel saraf tepi. Simpulan penelitian ini adalah pengobatan kombinasi gabapentin dan vitamin B12 lebih baik dalam memperbaiki rasa nyeri pada pasien neuropati diabetik dibanding dengan gabapentin saja.